Miniatur Rel Kereta Api Cerdas Indonesia Berbasis Arduino - Imam Ahmad; Ade Surahman; Ferico Octaviansyah Pasaribu; Arif Febriansyah (PTE FTK UIN Ar-Raniry, 2018)
In designing a system in facilitating the work in operating the door bar and the lights of the railroad tracks that sometimes require quite a lot of employees because this kind of problem often occurs because of negligence in operating a lot of accidents that occur in the railroad crossing. For this reason, the researchers designed a miniature intelligent railroad system that is expected to help streamline the operation of the doorstop and turn on the lights off the hallway automatically. The way this tool works is by utilizing the arduino microcontroller, the Infra Red sensor and the Ultrasonic sensor as the data input provider and the prototype's working method. The Infra Red 1 sensor will provide input when the train passes and the crossing bar will close, the Infra Red 2 sensor will open the crossbar the crossing door when the train has passed the crossing of the crossing door and gives a welcome message on the LCD, when the train enters the hallway the Ultrasonic sensor will turn on, control the led to adjust the net of the train that goes through the work process over and over.